Mechanism of Lysoforte in Improving Jejuna Morphology and Health in Broiler Chickens - Li, Xiaofeng; Shi, Xiaoli; Mesalam, Noura M.; Liu, Lei; Chen, Zhihao; Yang, Bing (Frontiers in Veterinary Science, 2022)
Lysoforte (LFT) plays a vital role in maintaining broilers' health and intestinal morphology. However, the mechanism behind the effects of LFT improving intestinal morphology and health is still unclear. Therefore, this study was implemented to explore the central genes linked to the regulatory effect of LFT. Thus, GSE94622 dataset consisted of the control and two LFT-treated groups (LFT500 and LFT1000) jejuna samples was obtained from Gene Expression Omnibus (GEO). Totally 106 to 344 DEGs were obtained by comparing LFT500 and LFT1000 vs. control and LFT1000 vs. LFT500. Gene ontology (GO) enrichment suggested that the DEGs mainly related to phosphatidylethanolamine biosynthetic process and neuron projection extension. KEGG analysis suggested the DEGs were enriched in AGE-RAGE, fatty acid elongation, ECM-receptor interaction (ECMRI), glycerophospholipid metabolism, focal adhesion, unsaturated fatty acids biosynthesis, and ABC transporters. Moreover, twenty-nine genes, such as REG4, GJB1, KAT2A, APOA5, SERPINE2, ELOVL1, ABCC2, ANKRD9, CYP4V2, and PISD, might be closely related to promoting jejuna morphology in broilers. Taken together, our observation enhances the understanding of LFT in maintaining intestinal architecture and the general health of broiler chickens.